Line planning in emergencies for railway networks. Issue 1 (28th January 2014) - Meng, Xuelei; Cui, Bingmou; Jia, Limin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to generate line plan in emergencies for railway networks to complete the passenger transportation. Design/methodology/approach – The authors first build a mathematical model, focusing on the frequency setting and stops setting. Then, considering the OD passenger flow data, the authors first propose the method to solve the train frequency setting problem of different types. Genetic algorithm is designed to solve the stops setting problem. The approach is tested with the data from Beijing-Shanghai high-speed railway and its neighbour existing railway. Findings – The authors find that the model is suitable to generate line plan in emergencies for railway networks and the algorithm has good calculating performance. Originality/value – The new algorithms to generate line plan proposed in this paper can be embedded in the decision support system for railway operators.